Under layer material and friction member
A phenolic resin composition with novolac-type phenolic resin, epoxy resin, and solid resol-type phenolic resin, combined with a thermosetting resin, addresses the issues of long molding times and rust in friction materials, ensuring robust adhesion and durability of friction members.
Patent Information
- Application Number
- JP2024105517
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-05
- Filing Date
- 2024-06-28
- Publication Date
- 2025-01-20
AI Technical Summary
Existing friction materials require long molding times and are prone to rust at the adhesive interface with the back plate, leading to decreased adhesiveness and potential gaps, which affect the strength and durability of the friction members.
The use of a phenolic resin composition comprising novolac-type phenolic resin, epoxy resin, and solid resol-type phenolic resin, combined with a thermosetting resin, as a binder in the underlayer material, to enhance adhesion and reduce rust resistance, allowing for shorter molding times without compromising strength.
The solution ensures strong adhesion between the pressure plate and the underlayer material even with reduced molding time, preventing gaps and rust, thereby maintaining the integrity and performance of the friction members.
Smart Images

Figure 2025010049000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an underlayer material for friction members used in automobiles, railway vehicles, industrial machines, and the like. [Background technology]
[0002] Friction materials are used in brakes such as disk brakes and drum brakes, or clutches, and perform braking by friction with a mating material such as a disk rotor.
[0003] Friction materials are usually bonded integrally to a metallic backing plate (pressure plate) that serves as a support, and are used as friction members such as disc brake pads. This bonding is generally performed by adhesion, and is generally performed simultaneously with molding of the friction material by heating and pressurizing the preformed friction material together with the backing plate. Here, from the viewpoint of improving adhesion to the backing plate and suppressing brake squeal, a technique is known in which the friction material is made into two layers with different constituent components, and the friction material placed on the pressure plate side (lower layer side) is called an underlayer material or underlay material. The underlayer material is particularly required to have adhesion between the pressure plate and the underlayer material on the lower layer side.
[0004] Patent Document 1 describes a friction material composition for underlayment that contains a heat-infusible phenolic resin as an organic filler. Patent Documents 2 and 3 describe friction materials having a two-layer structure. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2020 / 021644 [Patent Document 2] Japanese Patent Application Publication No. 07-292348 [Patent Document 3] Japanese Patent Application Publication No. 05-331452 Summary of the Invention [Problem to be solved by the invention]
[0006] In recent years, from the viewpoint of manufacturing efficiency, there has been a demand for shortening the time required for hot and cold molding. However, the techniques described in Patent Documents 1 to 3 require a molding time of about 5 minutes, leaving room for improvement. In addition, the presence of moisture during use can cause rust to form at the adhesive interface with the backing plate, reducing adhesion. For this reason, it is necessary to improve the rust resistance of the underlayer material and prevent the adhesiveness from decreasing.
[0007] An object of the present invention is to provide an underlayer material that can provide a friction member having ensured strength without generating a gap between the pressure plate and the underlayer material on the lower layer side even when the molding time is shortened, and a friction member having the underlayer material. [Means for solving the problem]
[0008] As a result of extensive investigations, the present inventors have found that the above-mentioned problems can be solved by using a specific phenolic resin composition and a thermosetting resin together as a binder.
[0009] That is, the present invention relates to the following underlayer material and friction member. [1] An underlayer material for use in a friction member, comprising a friction modifier, a binder, and a fibrous base material, the underlayer material comprising a phenolic resin composition as the binder, the phenolic resin composition containing a novolac-type phenolic resin, an epoxy resin, and a solid resol-type phenolic resin, and a thermosetting resin. Effect of the Invention
[0010] By using the underlayer material of the present invention, it is possible to ensure adhesion between the pressure plate and the underlayer material on the lower layer side during short-time molding, while suppressing reduction in strength due to heat history and combined cycle corrosion history. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of the structure of a friction member of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The present invention will be described in detail below, however, these are examples of preferred embodiments and the present invention is not limited to the contents thereof.
[0013] The underlayer material of the present invention is used in a friction member.
[0014] [Friction materials] As shown in FIG. 1, a friction member 10 includes a friction material 1, an underlayer material 2, and a pressure plate 3 in this order.
[0015] [Underlayer material] The underlayer material of the present invention comprises a friction modifier, a binder and a fibrous base material.
[0016] <Friction adjustment material> Examples of friction modifiers used in the underlayer material include inorganic fillers, organic fillers, abrasives, solid lubricants, and metal powders.
[0017] Examples of inorganic fillers include titanates such as potassium titanate, lithium titanate, lithium potassium titanate, sodium titanate, calcium titanate, magnesium titanate, and magnesium potassium titanate, as well as inorganic materials such as barium sulfate, calcium carbonate, calcium hydroxide, vermiculite, and mica. These may be used alone or in combination of two or more.
[0018] The inorganic filler is used in an amount of preferably 30 to 70 mass %, and more preferably 35 to 65 mass %, of the entire underlayer material.
[0019] Examples of organic fillers include various rubber powders (raw rubber powder, tire powder, etc.), rubber dust, resin dust, cashew dust, tire tread, melamine dust, etc. These may be used alone or in combination of two or more.
[0020] The organic filler is preferably used in an amount of 1 to 15 mass %, more preferably 1 to 10 mass %, based on the entire underlayer material.
[0021] Examples of the abrasive include zirconium oxide, alumina, silica, magnesium oxide, zirconia, zirconium silicate, chromium oxide, iron oxide (Fe3O4), chromite, etc. These may be used alone or in combination of two or more kinds, as required.
[0022] When an abrasive is blended in the underlayer material, the abrasive is preferably used in an amount of 1 to 20 mass %, more preferably 3 to 15 mass %, of the entire underlayer material.
[0023] Examples of solid lubricants include graphite, coke, antimony trisulfide, molybdenum disulfide, tin sulfide, polytetrafluoroethylene (PTFE), etc. These may be used alone or in combination of two or more kinds, as required.
[0024] When a solid lubricant is blended in the underlayer material, the solid lubricant is preferably used in an amount of 1 to 20 mass %, more preferably 3 to 15 mass %, of the entire underlayer material.
[0025] Examples of metal powders include powders of aluminum, tin, zinc, etc. These may be used alone or in combination of two or more.
[0026] The metal powder is preferably used in an amount of 1 to 10 mass %, more preferably 1 to 5 mass %, based on the entire underlayer material.
[0027] The friction modifier is preferably used in an amount of 30 to 80 mass %, more preferably 40 to 70 mass %, of the entire underlayer material.
[0028] <Binding material> The underlayer material of the present invention contains a phenolic resin composition (hereinafter also referred to as "specific phenolic resin composition") containing a novolac type phenolic resin, an epoxy resin, and a solid resol type phenolic resin as a binder, and a thermosetting resin. The specific phenolic resin composition has the advantage of being fast curing speed and capable of shortening the thermoforming time, but the heat resistance of the underlayer material is insufficient. By using the specific phenolic resin composition in combination with a thermosetting resin, the thermoforming time can be shortened and an underlayer material having good adhesiveness can be obtained. This is thought to be because the underlayer material can be manufactured without impairing the moldability by using the thermosetting resin with excellent heat resistance in combination.
[0029] The novolac-type phenolic resin used in the specific phenolic resin composition is usually obtained by reacting phenols and aldehydes in the presence of an acid catalyst such as hydrochloric acid or sulfuric acid at a reaction molar ratio (F / P) of phenols (P) to aldehydes (F) of 0.5 to 0.9.
[0030] The phenols are not particularly limited, and examples thereof include phenol, orthocresol, metacresol, paracresol, xylenol, para-tertiary butylphenol, paraoctylphenol, paraphenylphenol, bisphenol A, bisphenol F, and resorcinol, and phenol and cresol are usually used. Similarly, the aldehydes are not particularly limited, and examples thereof include aldehydes such as formaldehyde, acetaldehyde, butylaldehyde, and acrolein, or mixtures thereof. Substances that are sources of these aldehydes, or solutions of these aldehydes, can also be used, but formaldehyde is usually used. The form of the novolac phenolic resin thus obtained is not particularly limited, and any form such as liquid, solid, or powder can be used.
[0031] The amount of the novolac phenolic resin in the specific phenolic resin composition is not particularly limited, but is preferably 50 to 95 mass % and more preferably 60 to 90 mass % based on the total composition. If the amount of the novolac phenolic resin is equal to or less than the upper limit, the composition is cured sufficiently, and if it is equal to or more than the lower limit, the resin is not cured too quickly and the fluidity during molding is not reduced, so that the mechanical strength of the underlayer material is good.
[0032] The epoxy resin used in the specific phenolic resin composition is not particularly limited, but may be any resin having at least two epoxy groups in one molecule and being solid or liquid at room temperature, such as bisphenol A type, bisphenol S type, phenol novolac type, cresol novolac type, biphenyl type, naphthalene type, aromatic amine type, etc. These may be used alone or in combination.
[0033] The amount of epoxy resin in the specific phenolic resin composition is not particularly limited, but is preferably 1 to 50 mass % relative to the entire composition, and more preferably 5 to 40 mass %. If the amount of epoxy resin is within this range, the resin component is sufficiently cured, and sufficient mechanical strength as an underlayer material is obtained.
[0034] The solid resol-type phenolic resin used in the specific phenolic resin composition is usually prepared by reacting phenols and aldehydes in the presence of an alkaline catalyst such as an alkali metal hydroxide, a tertiary amine, an alkaline earth metal oxide or hydroxide, or an alkaline substance, such that the reaction molar ratio (F / P) of the aldehydes (F) to the phenols (P) is preferably 0.7 to 3.0, and more preferably 0.9 to 1.8.
[0035] The phenols used here are not particularly limited, but examples thereof include phenols such as phenol, orthocresol, meta-cresol, para-cresol, xylenol, para-tertiary butylphenol, para-octylphenol, para-phenylphenol, bisphenol A, bisphenol F, and resorcin, and phenol and cresol are usually used. Similarly, the aldehydes are not particularly limited, but examples thereof include aldehydes such as formaldehyde, acetaldehyde, butylaldehyde, and acrolein, or mixtures thereof. Substances that are sources of these aldehydes, or solutions of these aldehydes can also be used, but formaldehyde is usually used. The resol-type phenolic resin obtained in this manner is used in the form of a solid.
[0036] The amount of the solid resol type phenolic resin in the specific phenolic resin composition is not particularly limited, but is preferably 1 to 50 mass % and more preferably 5 to 40 mass % based on the total composition. When the amount of the solid resol type phenolic resin is equal to or more than the lower limit, the composition is cured sufficiently, and when the amount is equal to or less than the upper limit, the resin is not cured too quickly and the flowability during molding is not easily reduced, so that the mechanical strength of the cured product is not easily reduced.
[0037] In the present invention, the specific phenolic resin composition can be produced by melt-kneading raw materials including a novolac phenolic resin, an epoxy resin, a curing catalyst, and a solid resol phenolic resin. Here, it is preferable to melt-knead at least the novolac phenolic resin and the epoxy resin and / or the curing agent using a pressurized kneading device. Furthermore, it is more preferable to mix the novolac phenolic resin, the epoxy resin, the curing catalyst, and the solid resol phenolic resin uniformly in a state where the phenolic resin and the epoxy resin do not substantially cure when the novolac phenolic resin, the epoxy resin, the curing catalyst, and the solid resol phenolic resin are melted and flowing. The temperature during mixing is appropriately a temperature at which the phenolic resin and the epoxy resin melt but do not start curing. In addition, by using a pressurized kneading device, it is possible to uniformly disperse the phenolic resin, the epoxy resin, and the curing catalyst.
[0038] As the specific phenolic resin composition, for example, the phenolic resin composition described in JP-A-2008-222851 can be used.
[0039] The friction member according to the embodiment of the present invention contains a thermosetting resin as a binder. A thermosetting resin is a resin that has the property of going from a liquid state to a solid state when heat is applied. By including the specific phenolic resin composition and a thermosetting resin as a binder, the curing speed is increased by the specific phenolic resin composition, so that the time required for thermoforming the friction member can be shortened, and the heat resistance of the thermosetting resin improves the adhesion of the underlayer material.
[0040] Examples of the thermosetting resin include straight phenol resin, various modified phenol resins with elastomers, functional particulate phenol resins, melamine resins, epoxy resins, polyimide resins, etc. Examples of the elastomer-modified phenol resin include various modified phenol resins such as acrylic rubber-modified phenol resins, silicone rubber-modified phenol resins, and NBR rubber-modified phenol resins. These thermosetting resins can be used alone or in combination of two or more.
[0041] The thermosetting resin used as the binder is preferably a functional particulate phenolic resin from the viewpoint of improving adhesion. The functional particulate phenolic resin has a weight average molecular weight of 3,000 or more and has an appropriate amount of methylol groups in its molecular structure, so that it has excellent affinity and reactivity, and can obtain a friction member with improved mechanical strength. In addition, the functional particulate phenolic resin does not contain hexamethylenetetramine, so that gas generation during thermoforming or heat treatment is suppressed, and the occurrence of cracks in the friction member can be suppressed.
[0042] The functional particulate phenolic resin may be a commercially available product, such as "Bellpearl S899", "Bellpearl S890", "Bellpearl S870" or "Bellpearl S830" (trade names) manufactured by Air Water Performance Chemicals Inc.
[0043] The mass ratio of the specific phenol resin composition to the thermosetting resin is preferably 2:1 to 1:2, and more preferably 2:1 to 1:1. When the mass ratio is equal to or more than the lower limit, the resin cures at a sufficient rate, and when the mass ratio is equal to or less than the upper limit, the resin cures sufficiently, and as a result, an underlayer material having excellent adhesion can be obtained even when produced in a short thermoforming time.
[0044] The content of the specific phenolic resin composition in the underlayer material is preferably 1 to 10 mass %, more preferably 3 to 8 mass %. When the content of the specific phenolic resin composition is equal to or more than the lower limit, the resin curing speed is sufficient, and when the content is equal to or less than the upper limit, the moldability is good, and as a result, an underlayer material with excellent adhesion can be obtained even when thermoforming is performed in a short time.
[0045] The content of the thermosetting resin in the underlayer material is preferably 1 to 10 mass %, more preferably 3 to 8 mass %. When the content of the thermosetting resin is equal to or more than the lower limit, sufficient heat resistance is achieved, and when the content is equal to or less than the upper limit, stable moldability can be achieved. As a result, an underlayer material with excellent adhesiveness can be obtained even when produced in a short thermoforming time.
[0046] Furthermore, the total content of the specific phenolic resin composition and the thermosetting resin in the underlayer material is preferably 3 to 15 mass %, more preferably 6 to 12 mass %. When the total content is equal to or more than the lower limit, the resin is sufficiently cured, and when the total content is equal to or less than the upper limit, the moldability is good, which is preferable.
[0047] When the thermosetting resin is a straight phenol resin, the total content of the phenol resin contained in the specific phenol resin composition is preferably 1 to 15 mass % in the underlayer material.
[0048] The binder may contain other resins in addition to the specific phenol resin composition and thermosetting resin described above.
[0049] In order to ensure sufficient mechanical strength and adhesiveness, the content of the binder in the underlayer material is preferably 1 to 20 mass %, and more preferably 3 to 15 mass %.
[0050] <Fiber base material> Examples of the fiber base material used in the underlayer material include organic fibers, inorganic fibers, metal fibers, etc. Each of the fiber base materials may be used alone or in combination of two or more kinds.
[0051] Examples of organic fibers include aromatic polyamide (aramid) fibers and flame-resistant acrylic fibers.
[0052] Examples of inorganic fibers include biosoluble inorganic fibers, ceramic fibers, glass fibers, carbon fibers, rock wool, etc. Examples of biosoluble inorganic fibers include biosoluble ceramic fibers such as SiO2-CaO-MgO fibers, SiO2-CaO-MgO-Al2O3 fibers, and SiO2-MgO-SrO fibers, and biosoluble rock wool.
[0053] The metal fibers include, for example, steel fibers. It is preferable not to use copper fibers or bronze fibers that contain copper.
[0054] From the viewpoint of ensuring the strength of the underlayer material, the fiber base material is used in an amount of preferably 10 to 50 mass %, and more preferably 15 to 45 mass %, of the entire underlayer material.
[0055] The underlayer material according to the embodiment of the present invention may contain other materials as required in addition to the fiber base material, friction modifier, and binder.
[0056] However, from the viewpoint of reducing the environmental load, the underlayer material according to the embodiment of the present invention does not contain a copper component. "Does not contain a copper component" means that the copper component is substantially not contained, and does not exclude that the copper component is inevitably contained. More specifically, it means that the copper content as an element is 0.5 mass% or less.
[0057] The underlayer material according to an embodiment of the present invention contains a phenolic resin composition containing a novolac-type phenolic resin, an epoxy resin, and a solid resol-type phenolic resin as a binder, and a thermosetting resin, thereby achieving both a shortened thermoforming time and excellent adhesion.
[0058] [Friction material] The friction material includes a friction modifier, a binder, and a fibrous base material.
[0059] <Friction adjustment material> Friction modifiers are used in friction materials to impart desired friction characteristics, such as wear resistance, heat resistance, and fade resistance, to the friction materials.
[0060] Examples of friction modifiers include inorganic fillers, organic fillers, abrasives, solid lubricants, and metal powders.
[0061] Examples of inorganic fillers include titanates such as potassium titanate, lithium titanate, lithium potassium titanate, sodium titanate, calcium titanate, magnesium titanate, and magnesium potassium titanate, as well as inorganic materials such as barium sulfate, calcium carbonate, calcium hydroxide, vermiculite, and mica. These may be used alone or in combination of two or more.
[0062] The inorganic filler is preferably used in an amount of 30 to 80 mass %, more preferably 40 to 70 mass %, based on the entire friction material.
[0063] Examples of organic fillers include various rubber powders (raw rubber powder, tire powder, etc.), rubber dust, resin dust, cashew dust, tire tread, melamine dust, and the like. These may be used alone or in combination of two or more.
[0064] The organic filler is preferably used in an amount of 1 to 15 mass %, more preferably 1 to 10 mass %, based on the entire friction material.
[0065] Examples of the abrasive include zirconium oxide, alumina, silica, magnesium oxide, zirconia, zirconium silicate, chromium oxide, iron oxide trioxide (Fe3O4), chromite, etc. These may be used alone or in combination of two or more.
[0066] The abrasive is preferably used in an amount of 1 to 20 mass %, more preferably 3 to 15 mass %, based on the total mass of the friction material.
[0067] Examples of solid lubricants include graphite, coke, antimony trisulfide, molybdenum disulfide, tin sulfide, polytetrafluoroethylene (PTFE), etc. These may be used alone or in combination of two or more.
[0068] The solid lubricant is preferably used in an amount of 1 to 20 mass %, more preferably 3 to 15 mass %, based on the total mass of the friction material.
[0069] Examples of the metal powder include powders of aluminum, tin, zinc, copper, etc. These may be used alone or in combination of two or more.
[0070] The metal powder is preferably used in an amount of 1 to 10 mass %, more preferably 1 to 5 mass %, based on the entire friction material.
[0071] From the viewpoint of imparting the above-mentioned desired friction characteristics to the friction material sufficiently, the friction modifier is used in an amount of preferably 60 to 90 mass %, and more preferably 70 to 90 mass %, of the entire friction material.
[0072] <Binding material> The binder used in the friction material may be any of various commonly used binders, including phenolic resins, various modified phenolic resins such as elastomers, thermosetting resins such as melamine resins, epoxy resins, and polyimide resins, and the above-mentioned specific phenolic resin compositions used in the underlayer material.
[0073] Examples of elastomer-modified phenolic resins include acrylic rubber-modified phenolic resins, silicone rubber-modified phenolic resins, nitrile rubber (NBR)-modified phenolic resins, etc. These may be used alone or in combination of two or more.
[0074] From the viewpoint of formability of the friction material, the binder is preferably used in an amount of 1 to 20 mass %, more preferably 3 to 15 mass %, of the entire friction material.
[0075] <Fiber base material> Examples of the fibrous base material used in the friction material include organic fibers, inorganic fibers, metal fibers, etc. The fibrous base materials may be used alone or in combination of two or more kinds.
[0076] Examples of organic fibers include aromatic polyamide (aramid) fibers and flame-resistant acrylic fibers.
[0077] Examples of inorganic fibers include biosoluble inorganic fibers, ceramic fibers, glass fibers, carbon fibers, rock wool, etc. Examples of biosoluble inorganic fibers include biosoluble ceramic fibers such as SiO2-CaO-MgO fibers, SiO2-CaO-MgO-Al2O3 fibers, and SiO2-MgO-SrO fibers, and biosoluble rock wool.
[0078] The metal fibers include, for example, steel fibers. It is preferable not to use copper fibers or bronze fibers that contain copper.
[0079] From the viewpoint of ensuring the strength of the friction material, the fibrous base material is used in an amount of preferably 3 to 30 mass %, and more preferably 5 to 20 mass %, of the entire friction material.
[0080] From the viewpoint of reducing the environmental load, it is preferable that the friction material does not contain a copper component.
[0081] [Pressure plate] The pressure plate is formed by sheet metal pressing or the like. The material of the pressure plate is not particularly limited, and known iron metal materials can be used. For example, hot-rolled steel sheets for automobile structures such as SAPH400 and SAPH440, and hot-rolled high-tensile steel sheets for automobiles such as SPFH590 can be used.
[0082] [Method of manufacturing friction material, underlayer material and friction member] The friction material, underlayer material, and friction member can be manufactured by known manufacturing processes. For example, the above-mentioned components are blended, and the blend is subjected to processes such as preforming, thermoforming, heating, and polishing according to a conventional manufacturing method.
[0083] A method for manufacturing a friction member including a friction material, an underlayer material, and a pressure plate generally includes the following steps. (a) A process of forming a pressure plate into a desired shape using a sheet metal press. (b) A process of degreasing, chemical conversion and primer treatment on the pressure plate, and applying an adhesive. (c) A process in which the raw materials for the friction material and the raw materials for the underlayer material are separately blended, thoroughly homogenized by mixing, and each raw material is put into a predetermined mold in order, and the friction material and the underlayer material are integrally molded at room temperature under a predetermined pressure to produce a preform. (d) A thermoforming process in which the above preform and a pressure plate coated with adhesive are arranged so that the underlayer material side is in contact with the adhesive side, and a predetermined temperature and pressure are applied to bond both components together (forming temperature: 130 to 180°C, forming pressure: 30 to 80 MPa, forming time: 1 to 10 minutes). (e) After-curing (150-300°C, 1-5 hours) and final finishing such as polishing, scorching, and painting. Through these steps, the friction member according to the embodiment of the present invention can be manufactured. In particular, the molding time in step (d) has conventionally been preferably 4 minutes or more, and more preferably 5 minutes or more, but the friction member according to the present embodiment can be produced with excellent adhesion even in a molding time of 3 minutes or less.
[0084] The thickness of the friction material is preferably 4 to 15 mm, and more preferably 6 to 13 mm. The thickness of the underlayer material is preferably 1 to 4 mm, and more preferably 1 to 3 mm.
[0085] Based on the above, this specification discloses the following underlayer material and friction member. [1] An underlayer material for a friction member, comprising a friction modifier, a binder and a fibrous base material, The underlayer material contains a phenolic resin composition containing a novolac type phenolic resin, an epoxy resin, and a solid resol type phenolic resin as the binder, and a thermosetting resin. [2] The underlayer material according to [1], wherein a mass ratio of the phenolic resin composition to the thermosetting resin is 2:1 to 1:2. [3] The underlayer material according to [1] or [2], wherein the content of the phenol resin composition is 1 to 10 mass %. [4] The underlayer material according to any one of [1] to [3], wherein the content of the thermosetting resin is 1 to 10 mass %. [5] The underlayer material according to any one of [1] to [4], wherein the total content of the phenolic resin composition and the thermosetting resin is 3 to 15 mass %. [6] A friction member comprising a friction material, the underlayer material according to any one of [1] to [5], and a pressure plate, in this order. EXAMPLES
[0086] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples in any way.
[0087] (Examples 1-2, Comparative Examples 1-2) The compounding materials for the friction material and the compounding materials for the underlayer material shown in Table 1 were respectively placed in a mixer and mixed at room temperature for 4 minutes to obtain a mixture of the compounding materials for the friction material and a mixture of the compounding materials for the underlayer material.
[0088] The resulting mixture was subjected to the following steps of (i) preforming, (ii) thermoforming, and (iii) heat treatment and scorching to produce a friction member.
[0089] (i) Preforming The friction material compounded mixture and the underlayer material compounded mixture were sequentially placed in a preforming press die and molded at room temperature and 20 MPa for 10 seconds to prepare a preforming body. (ii) Thermoforming This preform was placed in a thermoforming mold, and a metal plate (pressure plate) to which an adhesive had been applied was placed on top of it, followed by heat and pressure molding at 150° C. and 50 MPa for 2 minutes. (iii) Heat treatment, scorch This hot-pressed compact was heat-treated at 250° C. for 3 hours, and then the surface was polished. Next, the surface of this hot-pressed molded product was subjected to a scorch treatment and finished by painting to obtain a friction member.
[0090] As the phenolic resin composition, a phenolic resin composition manufactured by Sumitomo Bakelite Co., Ltd. (a phenolic resin composition containing a total of 65 mass % of novolac type phenolic resin and solid resol type phenolic resin, and 35 mass % of epoxy resin) was used. As the thermosetting resin, straight phenolic resin manufactured by Sumitomo Bakelite Co., Ltd. or functional particulate phenolic resin manufactured by Air Water Performance Chemicals Inc. was used.
[0091] The adhesion of the obtained friction member was evaluated by the following method, and the results are shown in Table 1.
[0092] <Adhesion between pressure plate and underlayer material> The friction member was visually observed to check whether or not there was a gap between the pressure plate and the underlayer material. [Evaluation Criteria] ○: No gap ×: There is a gap
[0093] <Shear strength> The shear strength of the friction members was measured at room temperature and at a high temperature (300°C) in accordance with JIS D4422-2007. [Evaluation criteria at room temperature] ○: 500N / cm 2 End ×:500N / cm 2 less than [Evaluation criteria for 300℃] ○: 400N / cm 2 End ×:400N / cm 2 less than
[0094] <Shear strength after cyclic corrosion test (CCT)> A combined cyclic corrosion test (CCT) in accordance with JASO M609-1991 was performed for 60 cycles, and the shear strength at room temperature of the friction members after the test was measured in accordance with JIS D4422-2007. [Evaluation Criteria] ○: 500N / cm 2 End ×:500N / cm 2 less than
[0095] The results of each test are shown in Table 1.
[0096] [Table 1]
[0097] From the above results, the friction members of Example 1 and Example 2, which used an underlayer material containing a phenolic resin composition and a thermosetting resin as a binder, showed good adhesion because there was no gap between the pressure plate and the underlayer material and sufficient shear strength was obtained at room temperature and at high temperatures. Furthermore, the friction member of Example 2, which used a functional fine particle phenolic resin as the thermosetting resin, had a higher shear strength than the friction member of Example 1, which used a normal phenolic resin. The friction member of Comparative Example 1, which used an underlayer material containing only a thermosetting resin as a binder, did not have sufficient shear strength at room temperature and at high temperature.The friction member of Comparative Example 2, which used an underlayer material containing only a phenolic resin composition as a binder, did not have sufficient shear strength at high temperature.
[0098] (Examples 3 to 5) The compounding materials for the friction material and the compounding materials for the underlayer material shown in Table 2 were respectively placed in a mixer and mixed at room temperature for 4 minutes to obtain a mixture of the compounding materials for the friction material and a mixture of the compounding materials for the underlayer material.
[0099] The resulting mixture was subjected to the following steps of (i) preforming, (ii) thermoforming, and (iii) heat treatment and scorching to produce a friction member.
[0100] (i) Preforming The friction material compounded mixture and the underlayer material compounded mixture were sequentially placed in a preforming press die and molded at room temperature and 20 MPa for 10 seconds to prepare a preforming body. (ii) Thermoforming This preform was placed in a thermoforming mold, and a metal plate (pressure plate) to which an adhesive had been applied was placed on top of it, followed by heat and pressure molding at 150° C. and 50 MPa for 2 minutes. (iii) Heat treatment, scorch This hot-pressed compact was heat-treated at 250° C. for 3 hours, and then the surface was polished. Next, the surface of this hot-pressed molded product was subjected to a scorch treatment and finished by painting to obtain a friction member.
[0101] The obtained friction members were evaluated for adhesion to the base material, shear strength, and porosity by the following methods. The results are shown in Table 2.
[0102] <Adhesion between pressure plate and underlayer material> The friction members were subjected to shear tests at room temperature and at 300°C in accordance with JIS D4422-2007, and their adhesion was evaluated based on the fracture cross-sectional area of the base material (friction material) after the tests. [Evaluation Criteria] ◎: Base material fracture cross section is 100% ○: Base material fracture cross-sectional area is 95% or more but less than 100% ×: The fracture cross-sectional area of the base material is less than 95%
[0103] <Test piece (TP) shear strength> The TP shear strength of the friction members was measured in accordance with JASO C444-78. The test pieces of the underlayer material were prepared from the adhesive interface side with the pressure plate of a friction member (disc brake pad) with an underlayer material thickness of 5 mm. The test pieces of the friction material (base material) were prepared from the inside of the base material (the side close to the interface of the friction material with the underlayer material) of a friction member (disc brake pad) with a normal thickness of the underlayer material. The shear strength of the base material was 8.4 MPa. Compared with the shear strength of the base material, those with higher shear strength were rated as "high." Table 2 shows a comparison of the shear strength of the underlayer material and the shear strength of the base material.
[0104] <Porosity> The porosity of the underlayer material was measured by the oil impregnation method in accordance with JIS D 4418. Test pieces of the underlayer material were prepared in the same manner as in the evaluation of the shear strength of the test piece (TP).
[0105] The results of each test are shown in Table 2.
[0106] [Table 2]
[0107] From the above results, the friction members of Examples 3 to 5 had sufficient shear strength, and therefore showed good adhesion even when the ratio of the phenolic resin composition to the thermosetting resin was changed. In addition, the friction members of Examples 4 and 5, in which the total binder resin content in the underlayer material was 8% by mass, had slightly improved room temperature shear properties compared to Example 3, in which the total binder resin content was 11% by mass. This shows that the adhesion can be further improved by optimizing the amount of binder resin. The reason why the friction members of Examples 4 and 5 had higher room temperature shear properties than Example 3 is thought to be that the total binder resin content in the underlayer material of Examples 4 and 5 was lower than that of Example 3, resulting in a higher porosity of the underlayer material. [Explanation of symbols]
[0108] 1 Friction material 2 Underlayer material 3 Pressure Plate 10 Friction material
Claims
1. An underlayer material for use in a friction member, comprising a friction modifier, a binder, and a fibrous base material, The underlayer material contains a phenolic resin composition containing a novolac-type phenolic resin, an epoxy resin, and a solid resol-type phenolic resin as the binder, and a thermosetting resin.
2. The underlayer material according to claim 1, wherein a mass ratio of the phenolic resin composition to the thermosetting resin is from 2:1 to 1:
2.
3. The underlayer material according to claim 1, wherein the content of the phenolic resin composition is 1 to 10 mass %.
4. The underlayer material according to claim 1, wherein the content of the thermosetting resin is 1 to 10 mass %.
5. The underlayer material according to claim 1, wherein a total content of the phenolic resin composition and the thermosetting resin is 3 to 15 mass %.
6. A friction member comprising a friction material, the underlayer material according to any one of claims 1 to 5, and a pressure plate, in that order.
Citation Information
Patent Citations
Non-asbestos friction material
JP1993331452A
Frictional material
JP1995292348A
Friction member, friction material composition for lower layer materials, lower layer material and automobile
WO2020021644A1